2016
DOI: 10.1089/fpd.2016.2154
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation and Disinfectant Susceptibility of Persistent and Nonpersistent Listeria monocytogenes Isolates from Gorgonzola Cheese Processing Plants

Abstract: The aim of this study was to investigate whether the biofilm-forming ability and/or the disinfectant susceptibility accounted for the persistence of Listeria monocytogenes in Gorgonzola cheese processing plants. For this purpose, a set of 16 L. monocytogenes isolates collected in the 2004-2007 period was analyzed, including 11 persistent isolates collected in different years, within the collection period, and displaying identical or highly correlated pulsotypes. The evaluation of biofilm-forming ability was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…The evaluation of biofilm-forming ability was performed by quantification of biofilm biomass on microtiter plates (polystyrene), using both the crystal violet (CV) method (Borucki, Peppin, White, Loge, & Call, 2003) and a method of enumeration of viable cells on stainless steel coupons (SSC), as described by Costa et al (2016). Biofilms were grown in tryptic soy broth with 0.6% yeast extract (TSB-YE, Biokar Diagnostics, Beauvais, France) at 25 °C for 24 (CV) and 48 h (SSC).…”
Section: Evaluation Of Biofilm-forming Ability and Biofilm Susceptibimentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation of biofilm-forming ability was performed by quantification of biofilm biomass on microtiter plates (polystyrene), using both the crystal violet (CV) method (Borucki, Peppin, White, Loge, & Call, 2003) and a method of enumeration of viable cells on stainless steel coupons (SSC), as described by Costa et al (2016). Biofilms were grown in tryptic soy broth with 0.6% yeast extract (TSB-YE, Biokar Diagnostics, Beauvais, France) at 25 °C for 24 (CV) and 48 h (SSC).…”
Section: Evaluation Of Biofilm-forming Ability and Biofilm Susceptibimentioning
confidence: 99%
“…The evaluation of the biofilm susceptibility to the disinfectants was performed on biofilms grown on SCC in nutrient-limiting (1/10 diluted TSB-YE) and in nutrient-rich (TSB-YE) medium at 25 °C for 48 h, as described by Costa et al (2016). Two commercial HP-based disinfectants, commonly employed at the dairies where the isolates were collected, were used: P3-oxonia active (ECOLAB S.r.l) containing acetic acid and peracetic acid (designated herein as P3), and Mida San 315 (Christeyns Food Hygiene S.r.l) containing citric acid (designated herein as MS).…”
Section: Evaluation Of Biofilm-forming Ability and Biofilm Susceptibimentioning
confidence: 99%
See 1 more Smart Citation
“…However, an association between resistance to disinfectants and the persistence of the pathogen in different food processing environments has been demonstrated only in a few cases [11,52,[75][76][77][78]. A clear link between persistence and increased disinfectant resistance was not recorded in some other studies [65,68,[79][80][81]. To the best of our knowledge, this is the first report where the greater susceptibility to biocides of the biofilms by L. monocytogenes was observed in the case of the group of persistent strains ( Table 2).…”
Section: The Effect Of Disinfectants On Biofilmsmentioning
confidence: 83%
“…Some studies showed that persistent strains of L. monocytogenes formed more biofilm than non-persistent strains [5,13,49,52,54,64,65]. Others observed no difference between persistent strains as opposed to sporadic strains [44,[65][66][67][68]. Thus, the association between the ability of L. monocytogenes strains to form biofilms and their persistence in a food-processing plant environment is not clear.…”
Section: Capacity Of Strains Of L Monocytogenes To Form Biofilmmentioning
confidence: 99%